Effects of High-Pressure Homogenization on Pectin Structure and Cloud Stability of Not-From-Concentrate Orange Juice - Yu, Wantong; Cui, Jiefen; Zhao, Shaojie; Feng, Liping; Wang, Yanqi; Liu, Junmei; Zheng, Jinkai (Frontiers in Nutrition, 2021)
Not-from-concentrate (NFC) juice is popular with consumers due to its similarity to fresh fruit juice in taste, flavor, and beneficial nutrients. As a commonly used technology in fruit juice production, high-pressure homogenization (HPH) can enhance the commercial value of juice by improving the color, flavor, taste, and nutrient contents. In this study, the effects of HPH on the pectin structural properties and stability of NFC orange juice were investigated. The correlations between HPH-induced changes in the structure of pectin and the stability of orange juice were revealed. Compared with non-homogenized orange juice, HPH increased the galacturonic acid (GalA) content and the linearity of pectin, while decreasing the molecular weight (Mw), pectin branching, and rhamnogalacturonan (RG) contribution, and cracks and pores of different sizes formed on the surface of pectin, implying depolymerization. Meanwhile, with increasing pressure and number homogenization of passes, HPH effectively improved the stability of NFC orange juice. HPH can effectively prevent the stratification of orange juice, thereby promoting consumer acceptance and endowing a higher commercial value. The improvement of the stability of NFC orange juice by HPH was related to the structural properties of pectin. Turbidity was significantly (P < 0.01) positively correlated with GalA and pectin linearity, but was significantly (P < 0.01) negatively correlated with Mw, RG contribution, and pectin branching. Modification of pectin structure can improve the stability of NFC orange juice. In this work, the relationship between the pectin structure and stability of NFC orange juice is elucidated, providing a path toward improving consumer acceptance and enhancing the palatability and nutritional and functional qualities of orange juice. Manufacturers can use this relationship to modify pectin directionally and produce high-quality NFC orange juice beverages.